2001
DOI: 10.2116/analsci.17.1413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrolytes on the Configuration Change of Cobalt(II)-Halide Complexes in Chloroform/Water Reverse Micelle Systems

Abstract: As nanometer-size water droplets or "water pools," relatively large amounts of water can be stabilized in nonpolar organic solvents by a variety of surfactants; this kind of micelle system is called a reversed or reverse micelle. 1 The size of the "water pool" may vary from ~1 nm to ~10 nm, as a linear function of the W value, where W = [H2O]/[surfactant]. 1,2 The "water pools" provide very specific reaction fields; many studies have demonstrated that the water in "water pool" in reverse micelles considerably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…This observed Raman signal increase upon addition of a salt might be due to solvation or changes in the pH value. Similar observations have been reported by Nagayama et al, who observed intensity changes within the Raman spectrum of D 2 O upon addition of LiBr.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This observed Raman signal increase upon addition of a salt might be due to solvation or changes in the pH value. Similar observations have been reported by Nagayama et al, who observed intensity changes within the Raman spectrum of D 2 O upon addition of LiBr.…”
Section: Resultssupporting
confidence: 90%
“…This observed Raman signal increase upon addition of a salt might be due to solvation or changes in the pH value. Similar observations have been reported by Nagayama et al, 42 who observed intensity changes within the Raman spectrum of D 2 O upon addition of LiBr. Figure 4B−E summarizes the results of the influence of an activation salt in combination with a metal colloid on the observed melamine Raman peak area at 685 cm −1 .…”
Section: Resultssupporting
confidence: 90%
“…8 we observed that a rather strong yellow-color developed only when (dilute) nitric acid was present in Br À ion rich conditions; the possibility of formation of yellow-colored cobalt(II) and cobalt(III) complexes was denied by our careful examination of many cobalt complexes. Kimura et al 20,21 have reported the reactions of nitrous and phosphinic acids with the iodide ion in the presence of molecular oxygen in acidic solutions.…”
mentioning
confidence: 72%
“…The amounts of acidic impurities (e.g., R 3 NH þ ) in CTAB and CTAC were evaluated to be %0:03 and %0:05 mol %, respectively. 8 Chloroform was obtained from Wako and Aldrich as GR grade and ACS reagent grade, containing 0.3-1.0% ethanol and amylenes as the stabilizer, respectively. The chloroform containing ethanol as the stabilizer was used in the experiments, unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation